Closing the R&D gap: Evaluating the sources of R&D spending - Thomas Karier (Levy Economics Institute of Bard College, 1995)
Both spending and tax policies have been implemented in the United States with the goal of stimulating private sector research and development (R&D). Thomas Karier questions whether current R&D policy, especially the research and experimentation tax credit, can contribute to closing the gap between nondefense expenditures on R&D in the United States and such expenditures in other countries, such as Japan and Germany. He also explores possible changes to our current R&D policy to make it more effective.
Keywords: 330